2002
DOI: 10.2320/matertrans.43.2706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Crystallinity on Hydriding-Dehydriding and Charge-Discharge Characteristics of MgNi Alloy-Carbon Material Composites

Abstract: Hydriding-dehydriding and charge-discharge characteristics of amorphous MgNi alloys modified by ball-milling with different carbon materials were investigated with the intention of using them in nickel-metal hydride batteries. It was found that the ball-milling with carbon materials markedly improved hydriding-dehydriding and charge-discharge characteristics of the MgNi alloy, and an optimum ball-milling time was shortened by utilization of carbon material with lower crystallinity. However, ball-milling for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One is bulk modification, that is partial substitution of constituent elements with foreign metals, [8][9][10][11][12][13][14][15][16][17][18] and another is surface modification. [19][20][21] We have found that the discharge capacity was increased by surface modification, i.e., ballmilling of MgNi with carbon materials such as graphite, Ketjen black, etc., [22][23][24][25][26] while cycle performance was improved by bulk modification, i.e., partial substitution of Mg in a MgNi alloy with Ti and/or V in the ballmilling. 24,25,27 It was concluded that the Mg 0.9 Ti 0.06 V 0.04 Ni alloy was the most appropriate composition from the viewpoint of both discharge capacity and cycle performance.…”
mentioning
confidence: 99%
“…One is bulk modification, that is partial substitution of constituent elements with foreign metals, [8][9][10][11][12][13][14][15][16][17][18] and another is surface modification. [19][20][21] We have found that the discharge capacity was increased by surface modification, i.e., ballmilling of MgNi with carbon materials such as graphite, Ketjen black, etc., [22][23][24][25][26] while cycle performance was improved by bulk modification, i.e., partial substitution of Mg in a MgNi alloy with Ti and/or V in the ballmilling. 24,25,27 It was concluded that the Mg 0.9 Ti 0.06 V 0.04 Ni alloy was the most appropriate composition from the viewpoint of both discharge capacity and cycle performance.…”
mentioning
confidence: 99%
“…18 Ball milling of carbon materials has been used as a strategy to produce carbon-based hydrogen storage materials, [19][20][21][22] and carbon-metal hydrogen storage composites. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The performance of ball milled carbon composites is generally a function of ball-milling time, the presence of a solvent during processing, [23][24][25][26][27] and the breakdown of the graphitic structure. 25,31,38 Graphitic carbon becomes rapidly amorphitized during milling, evidenced by a rapid decrease in the characteristic graphite 002 (2θ=26º) reflection in X-ray diffraction (XRD).…”
Section: Introductionmentioning
confidence: 99%
“…28 The effect of temperature on cumulative pore volume and cumulative surface area of pyrolyzed Red Hills lignite…”
mentioning
confidence: 99%
“…However, the lower theoretical discharge capacity impedes their practical application. Subsequently, Zr-based or Ti-based alloys [4], V-based solid solution alloys [5] and Mg-based amorphous alloys [6,7] were extensively studied. However, Ti-based or Zr-based anodes need too many charge/discharge cycles to achieve their maximum discharge capacities, while Mg-based anodes quickly lose their discharge capacities because of the corrosion of Mg in KOH electrolyte [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%